Non-canonical bases differentially represented in the sex chromosomes of the dioecious plant Silene latifolia - Hubinský, Marcel; Hobza, Roman; Starczak, Marta; Gackowski, Daniel; Kubát, Zdeněk; Janíček, Tomáš; Horáková, Lucie; Rodriguez Lorenzo, Jose Luis (Journal of experimental botany, 2024)
The oxidation of 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC), and 5-carboxylcytosine (5caC), known as oxi-mCs, garners significant interest in plants as potential epigenetic marks. While research in mammals has established a role in cell reprogramming, carcinogenesis, and gene regulation, their functions in plants remain unclear. In rice, 5hmC has been associated with transposable elements (TEs) and heterochromatin. This study utilizes Silene latifolia, a dioecious plant with heteromorphic sex chromosomes and a genome with a large proportion of TEs, which provides a favourable environment for the study of oxi-mCs in individual sexes. Notably, we detected surprisingly high levels of oxi-mCs in S. latifolia comparable with mammals. Nuclei showed enrichment in heterochromatic regions, except for 5hmC whose signal was homogeneously distributed. Intriguingly, the same X chromosome in females displayed overall enrichment of 5hmC and 5fC compared with its counterpart. This fact is shared with 5mC, resembling dosage compensation. Co-localization showed higher correlation between 5mC and 5fC than with 5hmC, indicating no potential relationship between 5hmC and 5fC. Additionally, the promoter of several sex-linked genes and sex-biased TEs clustered in a clear sex-dependent way. Together, these findings unveil a hypothetical role for oxi-mCs in S. latifolia sex chromosome development, warranting further exploration.
Keywords: Cytosine modifications; oxi-mCs; Silene latifolia; transposable elements; epigeneze genetická; Sex Chromosomes; sex chromosomes; 5-Methylcytosine; pohlavní chromozomy; transpozibilní elementy DNA; DNA Transposable Elements; dosage compensation; Silene; 5-methylcytosin; chromozomy rostlin; Epigenesis, Genetic; Chromosomes, Plant